Low Level of Microsatellite Instability Correlates with Poor Clinical Prognosis in Stage II Colorectal Cancer Patients - Ehsan Nazemalhosseini Mojarad (Journal of Oncology, 2016)
The influence of microsatellite instability (MSI) on the prognosis of colorectal cancer (CRC) requires more investigation. We assessed the role of MSI status in survival of individuals diagnosed with primary colorectal cancer. In this retrospective cross-sectional study the MSI status was determined in 158 formalin-fixed paraffin-embedded tumors and their matched normal tissues from patients who underwent curative surgery. Cox proportional hazard modeling was performed to assess the clinical prognostic significance. In this study we found that MSI-H tumors were predominantly located in the colon versus rectum (p=0.03), associated with poorer differentiation (p=0.003) and TNM stage II/III of tumors (p=0.02). In CRC patients with stage II, MSI-L cases showed significantly poorer survival compared with patients who had MSI-H or MSS tumors (p=0.04). This study indicates that MSI-L tumors correlate with poorer clinical outcome in patients with stage II tumors (p=0.04) or in tumors located in the colon (p=0.02). MSI-L characterizes a distinct subgroup of CRC patients who have a poorer outcome. This study suggests that MSI status in CRC, as a clinical prognostic marker, is dependent on other factors, such as tumor stage and location.